NATIONAL MODEL OF ECONOMIC REFORMS AND NEW UZBEKISTAN STRATEGY (Marketing Journal, 2025)
This paper analyzes the socio -economic measures implemented within the framework of Uzbekistan’s national model of economic reforms and the “New Uzbekistan” strategy. The study examines key reforms, institutional changes, and macroeconomic adjustments aime d at promoting sustainable growth, improving the business environment, and enhancing social well -being. The findings demonstrate the effectiveness of the national reform model and offer recommendations for shaping future economic policy.
Keywords: Economic reforms; national model; New Uzbekistan strategy; macroeconomic policy; investment environment; institutional changes; sustainable development. № 1 63